Andreas Alariesto 1900-1989 - Kuusikko, Riitta; Ars Nordica (Ars Nordica, ISSN 0786-1478, 1994)
English summary.
Keywords: Alariesto, Andreas, : 1900-1989; 1900-luku; 1900-talet; henkilöhistoria; taidemaalarit; naivismi; maalaustaide; aiheet; kuvataide; saamelaiset; kulttuuri; maalaukset; kulttuurihistoria; kansatiede; personhistoria; målare (konstnärer); naivism; målarkonst; ämnen (områden); bildkonst; samer; kultur; målningar; kulturhistoria; etnologi; Lappi; Suomi; Finland; Lappland; Alariesto, Andreas